2019
DOI: 10.1002/mc.23007
|View full text |Cite
|
Sign up to set email alerts
|

Purpurogallin is a novel mitogen‐activated protein kinase kinase 1/2 inhibitor that suppresses esophageal squamous cell carcinoma growth in vitro and in vivo

Abstract: Purpurogallin is a natural compound that is extracted from nutgalls and oak bark and it possesses antioxidant, anticancer, and anti‐inflammatory properties. However, the anticancer capacity of purpurogallin and its molecular target have not been investigated in esophageal squamous cell carcinoma (ESCC). Herein, we report that purpurogallin suppresses ESCC cell growth by directly targeting the mitogen‐activated protein kinase kinase 1/2 (MEK1/2) signaling pathway. We found that purpurogallin inhibits anchorage‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…Therefore, efforts to develop new inhibitors able to block KDM4A activity and inhibit cancer cell proliferation are increasing. Purpurogallin 9aa, already described as an antiinflammatory, antioxidant, and anticancer agent (Wu et al, 1996;Kitada et al, 2003;Leone et al, 2003;Sang et al, 2004;Cheng et al, 2012;Xie et al, 2019), was found to be a KDM4A inhibitor. Based on the structure of 9aa, we synthesized a set of derivatives and analogs by changes on the starting phenol ring.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, efforts to develop new inhibitors able to block KDM4A activity and inhibit cancer cell proliferation are increasing. Purpurogallin 9aa, already described as an antiinflammatory, antioxidant, and anticancer agent (Wu et al, 1996;Kitada et al, 2003;Leone et al, 2003;Sang et al, 2004;Cheng et al, 2012;Xie et al, 2019), was found to be a KDM4A inhibitor. Based on the structure of 9aa, we synthesized a set of derivatives and analogs by changes on the starting phenol ring.…”
Section: Discussionmentioning
confidence: 95%
“…This compound belongs to the family of benzotropolone-containing natural products (Nierenstein and Swanton, 1944; Barltrop and Nicholson, 1948;Arpin et al, 1974;Klostermeyer et al, 2000;Kerschensteiner et al, 2011;Matsuo et al, 2017) and was already known to display antioxidant (Wu et al, 1996) and anticancer activities (Kitada et al, 2003;Leone et al, 2003), and to play a role in the modulation of inflammatory responses (Sang et al, 2004). Purpurogallin and its synthetic analogs were more recently reported to function as inhibitors of Toll-like receptors 1/2 (Cheng et al, 2012), and to modulate mitogen-activated protein kinase 1/2 signaling pathway, reducing esophageal squamous cell carcinoma growth (Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorphytum comosum (Thunb). Jacques (Spider Ivy) is a well-known plant for its ornamental value worldwide however based on ethanopharmacological evidence it has documented to be used in traditional Chinese medicine preparations for treatment of respiratory ailments, fracture and burns [3][4] [25].Thus, to best of our knowledge our study is the first systematic and comparative profiling of the plant marking the presence of other anticancer active molecules than saponins , however this is the initial screening which needs to be further validated by isolation and characterization studies to find out the lead molecules involved in anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid, ellagic acid, β-sitosterol, amentoflavone and purpurogallin were most frequently investigated and considered as the antioxidant compounds of Galla Chinensis. Their protective role in preventing various oxidative damage diseases have widely reported toward the various application potentials in recent years (Chen et al, 2018;Farbood et al, 2019;Kahkeshani et al, 2019;Ponnulakshmi et al, 2019;Xie et al, 2019). However, as the complex plant-insect symbiont, bioactive processes during galls formation suppose to generate abundance of bioactive metabolites in Galla Chinensis.…”
Section: Introductionmentioning
confidence: 99%